2021
DOI: 10.3389/fpls.2021.748273
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Changes in the Developing Rice Seeds Under Salt Stress Suggest Targets for Manipulating Seed Quality

Abstract: Global sea-level rise, the effect of climate change, poses a serious threat to rice production owing to saltwater intrusion and the accompanying increase in salt concentration. The reclaimed lands, comprising 22.1% of rice production in Korea, now face the crisis of global sea-level rise and a continuous increase in salt concentration. Here, we investigated the relationship between the decrease in seed quality and the transcriptional changes that occur in the developing rice seeds under salt stress. Compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 73 publications
(119 reference statements)
0
4
0
Order By: Relevance
“…Seed germination represents the initial stage in the life cycle of seed plants [25]. Climate change, improper fertilization, and irrigation tend to enhance soil salinity, posing new challenges to the seed germination and seedling development capacities of many land plants [26], including licorice.…”
Section: Discussionmentioning
confidence: 99%
“…Seed germination represents the initial stage in the life cycle of seed plants [25]. Climate change, improper fertilization, and irrigation tend to enhance soil salinity, posing new challenges to the seed germination and seedling development capacities of many land plants [26], including licorice.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that the expression of genes related to RFO metabolites is significantly upregulated under stress conditions such as low temperature, drought, and high salt. These findings suggest that RFOs may have a crucial effect on enhancing resistance to abiotic stresses ( Joshi et al., 2021 ; Lee et al., 2021 ). In addition, studies have reported that RFOs can facilitate the elimination of reactive oxygen species (ROS) in plants experiencing stress ( Ma et al., 2021 ).…”
Section: Introductionmentioning
confidence: 87%
“…60 One possible explanation is that 4 dS m −1 is too mild to trigger these effects. This assumption is supported by a paddy field experiment conducted on a reclaimed land using a "japonica" rice genotype, 61 which showed that even a minor increase in salinity from 4.00 to 4.17 dS m −1 can promote the upregulation of genes involved in the biosynthesis and accumulation of prolamin and glutelin.…”
Section: Nutrients Involved In the Storage Protein Content And Compos...mentioning
confidence: 99%